2014
DOI: 10.1007/s00520-014-2303-3
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for preparing patients for chemotherapy and radiotherapy: a systematic review

Abstract: Providing preparatory information can improve patient-reported outcomes in cancer patients undergoing chemotherapy and radiotherapy, especially with respect to satisfaction and knowledge. Some, but not all, studies improved psychological outcomes and physical symptoms. There is a need for methodologically rigorous research to determine the most effective timing and method of delivery of preparatory information to improve patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 50 publications
3
54
0
Order By: Relevance
“…In line with the present results Waller et al [3] indicated that providing preparatory information can improve knowledge in cancer patients undergoing chemotherapy. Furthermore, Dang et al [19] recommended pre-chemotherapy counseling to improve patient knowledge and understanding of the chemotherapy regimen received.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In line with the present results Waller et al [3] indicated that providing preparatory information can improve knowledge in cancer patients undergoing chemotherapy. Furthermore, Dang et al [19] recommended pre-chemotherapy counseling to improve patient knowledge and understanding of the chemotherapy regimen received.…”
Section: Resultssupporting
confidence: 91%
“…Patient who receive little or incomplete information may experience more sever side-effects. [3] Various cancer patients often do not understand and remember greatly of the information they receive within a medical consultation and state dissatisfaction with the amount and feature of information given to them about their disease and treatment. As a result of this, these patients express poorly compliance with treatment and less coping with their disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A computerised search of major psychological, medical, and nursing literature and doctoral theses databases with a moderate degree of overlap was conducted starting at 1959 where possible as the year of first transplantation : PsycINFO (1959 to December Week 4, 2014), MEDLINE (1959 to December Week 4, 2014), EMBASE (1974 to 2014 Week 52), CINAHL (1982 to December 30, 2014), and ProQuest Theses (1959 to December 30, 2014). Search terms were identified from a range of sources including systematic reviews of psychological interventions and distress in HSCT and analogous populations and during preliminary scoping of the literature [e.g. ], and relevant subject headings via the databases.…”
Section: Methodsmentioning
confidence: 99%
“…A recent systematic review on interventions for preparing patients for chemotherapy and radiotherapy highlighted the need for rigorous studies to provide further evidence to guide the preparation of patients for radiotherapy 22. Although a number of researchers have developed information resources (eg, videos and written information) for patients who require radiotherapy,23–26 the aim of these studies has been to provide general information about radiotherapy and side effects rather than specific information on what to expect at each stage and focusing on addressing patients’ anxiety.…”
Section: Introductionmentioning
confidence: 99%